2020
DOI: 10.1007/s00068-020-01319-y
|View full text |Cite
|
Sign up to set email alerts
|

Lagos state ambulance service: a performance evaluation

Abstract: Objectives The mortality rate from road traffic accidents (RTAs) in Nigeria is almost double that of the USA. In Nigeria, the first emergency medical services (EMS) system was established in March 2001, The Lagos State Ambulance Service (LASAMBUS). The objectives of this study are to (1) determine the burden of RTAs in Lagos, (2) assess RTA call outcomes, and (3) analyze LASAMBUS's response time and causes for delay. Methodology We reviewed completed LASAMBUS intervention forms spanning December 2017 to May 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…, 2018 ). While this might be the case in certain instances, the traffic contributes to delays for Lagos ambulances in 60% of cases ( Venkatraman et al. , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2018 ). While this might be the case in certain instances, the traffic contributes to delays for Lagos ambulances in 60% of cases ( Venkatraman et al. , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although Nigeria is among one-third of African countries that have emergency medical services (EMS) [ 36 ], there are lingering problems with EMS coverage, immediate availability and awareness of the public about EMS operations [ 37 ]. The time from activation of emergency medical services to response is between 15 and 35 min [ 37 , 38 ] which is longer than [8 min] recommended by the World Health Organization (WHO) [ 39 ]. Government-funded EMS suffer from poor maintenance and lack of infrastructure and medical consumables [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Government-funded EMS suffer from poor maintenance and lack of infrastructure and medical consumables [ 37 ]. Venkatraman et al [ 38 ] also identified traffic congestion and bad roads as contributing factors to the poor response rate of the Lagos State ambulance service.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first nationwide study documenting the impact of a newly developed EMS on health service utilization rates in a LIC. Although previous studies performed in low- and lower middle-income African countries attempted to evaluate the few existing referral systems, analyses were restricted to the local, district, or regional level [ 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Ghana, for example, poor communication between referrers and receivers has been shown to undermine the entire referral process [ 33 , 37 ]. Additionally, despite being key to assess the status and the performance of the entire EMS system, monitoring and quality assurance programs are frequently either absent or only partially developed among African LICs [ 9 , 34 ]. Our results indicate that almost all patients transported to hospital facilities met the priority criteria identified for NEMS interventions, suggesting a high compliance with the NEMS standard operating procedures for referrals and effective communication at different levels.…”
Section: Discussionmentioning
confidence: 99%